STRATEGI PENGEMBANGAN WISATA KULINER DI WADUK JATIGEDE KECAMATAN JATIGEDE KABUPATEN SUMEDANG - Lisnani Nur Alia, - (2021)
The Jatigede Reservoir is a popular tourist site in West Java's Sumedang Regency. It has a lot of natural resources, making it a place that has diverse culinary tourism potential. The purpose of this study is to determine the potential for culinary tourism in the Jatigede tourist destination, and how the strategy for developing culinary tourism in the Jatigede Reservoir tourist destination, Jatigede District, Sumedang Regency. The method used in this study is mixed-method study which is a combines both qualitative and quantitative approaches with data collection techniques is data triangulation, then analyzed using SWOT analysis.